A Roadmap for the Comparison of Identity Management Solutions Based on State-of-the-Art IdM Taxonomies - Madhan Kumar, Srinivasan; Rodrigues, Dr. Paul (Recent Trends in Network Security and Applications, 2010)
In recent days, digital identity in a corporate environment needs to be treated with high priority. Irrespective of different applications we use in organization, resources need to be managed and allotted to the appropriate identity/user (i.e. Provisioning Management) with proper access rights (Access Management). Identity management or IdM refers to how humans are identified, authorized and managed across computer networks. It deals with issues such as creating identities to the users, different ways to protect those identities & related information and the technologies supporting that protection. This paper analyzes the latest IdM product vendors in today’s market. Also this paper aims to provide a survey/roadmap to compare the identity management solutions based on various important identity factors. In this paper, we are analysing different IdM systems based on two state-of-the-art identity management taxonomies, such as features & capabilities and strategy & vision.